PRODUKTIFITAS DAN PENDAPATAN PETANI SWADAYA, PLASMA, DAN PERUSAHAAN BESAR SWASTA (STUDI KASUS DI PROPINSI KALIMANTAN TIMUR) - Zulkarnain Zulkarnain; Muhammad Erwan Suriaatmaja; Abdul Rahmi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The development of oil palm plantations in East Kalimantan can encourage the improvement of the regional economy and the people's economy.  The interest of farmers to cultivate oil palm plantations is quite large, however, the production results are not in line with expectations.  The purpose of this study is to determine the differences in productivity and income between independent smallholders, plasma, and large private companies. This research is a qualitative descriptive study referring to quantitative and comparative studies.  It was conducted in 5 districts namely, Kutai Kartanegara, Kutai Timur, Penajam Paser Utara, Paser, and Berau in the largest oil palm plantation area in East Kalimantan. The results showed that (1) the productivity of oil palm plantations on large private- and plasma- plantations continued to increase until the age of more than 10 years, while in smallholder self-help plantations the highest productivity was at the age of 9 years, after that there was a decrease in productivity; and (2) the income of large private plantations and plasma plantations continues to increase until the age of the plant is > 10 years, while in smallholder plantations the highest income occurs at the age of 9 years.